High-k gate dielectric materials : applications with advanced metal oxide semiconductor field effect transistors (MOSFETs) - Maity, Niladri Pratap; Maity, Reshmi; Baishya, Srimanta (Burlington, ON, Canada ; Palm Bay, Florida, USA : Apple Academic Press, 2020)
"This volume explores and addresses the challenges of high-k gate dielectric materials, one of the major concerns in the evolving semiconductor industry and the International Technology Roadmap for Semiconductors (ITRS). The application of high-k gate dielectric materials is a promising strategy that allows further miniaturization of microelectronic components (or Moore's law). This book presents a broad review of SiO2 materials, including a brief historical note of Moore's law, followed by reliability issues of the SiO2 based MOS transistor. Then it discusses the transition of gate dielectrics with an EOT ~ 1 nm and a selection of high-k materials. A review of the different deposition techniques of different high-k films is also discussed. High-k dielectrics theories (quantum tunneling effects and interface engineering theory) and applications of different novel MOSFET structures, like tunneling FET, are also covered in this book. The volume also looks at the important issues in the future of CMOS technology and presents an analysis of interface charge densities with the high-k material tantalum pentoxide. The issue of CMOS VLSI technology with the high-k gate dielectric materials is covered as is the advanced MOSFET structure, with its working, structure, and modeling. This timely volume addresses the challenges of high-k gate dielectric materials and will prove to be a valuable resource on both the fundamentals and the successful integration of high-k dielectric materials in future IC technology. Key features: Discusses the state-of-the-art in high-k gate dielectric research for MOSFET in the nanoelectronics regime, reviews high-k applications in advanced MOS transistor structures, considers CMOS IC fabrication with high-k gate dielectric materials."--
Moore's Law: In the 21st Century / N.P. Maity and Reshmi Maity -- SiO2-Based MOS Devices: Leakage and Limitations / N.P. Maity and Reshmi Maity -- High-k Dielectric Materials: Structural Properties and Selection / P. Sri Harsha, K. Venkata Saravanan, and V. Madhurima -- Selection of High-k Dielectric Materials / N.P. Maity and Reshmi Maity -- Tunneling Current Density and Tunnel Resistivity: Application to High-k Material HfO2 / N.P. Maity and Reshmi Maity -- Analysis of Interface Charge Density: Application to High-k Material Tantalum Pentoxide / N.P. Maity and Reshmi Maity -- High-k Material Processing in CMOS VLSI Technology / Partha Pratim Sahu -- Tunnel FET: Working, Structure, and Modeling / Srimanta Baishya -- Heusler Compound: A Novel Material for Optoelectronic,Thermoelectric, and Spintronic Applications / D.P. Rai.
OCLC-licensed vendor bibliographic record.
Keywords: Gate array circuits -- Materials; Metal oxide semiconductors -- Materials; Dielectrics; SCIENCE / General; SCIENCE / Physics; TECHNOLOGY / Electronics / Microelectronics